Penerapan Metode Simple Additive Weighting (SAW) Dalam SPK Pencarian Perumahan Residence - Dede Supriyadi; Dani (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
The high demand for houses in the Cibening Pamijahan Bogor area means that consumers must be careful in choosing a house that suits their needs. This is because many consumers do not understand the criteria for selecting a house. So far, consumers have only relied on information from other people or observations without considering the required criteria. Therefore, prospective buyers must carry out the house selection process correctly so as not to make the wrong decision. Field observations show that consumers when choosing housing usually consider at least four factors, namely price, location, facilities, environment and house design. This research aims to develop a decision support system that uses the SPK method to assist consumers in choosing housing. The design of this housing search decision support system uses an object-oriented approach using UML. This system was built using the PHP programming language and MySQL as the database. The results of this research are to make appropriate decisions based on information on the criteria or needs of potential buyers. The conclusion shows that the proposed system has the potential to be an effective tool in supporting the Housing Selection process in the Cibening Pamijahan Bogor area. And has the potential to have a positive impact on the people of Bogor, especially users who are confused about choosing housing. By using the SAW method, it is hoped that this system can provide recommendations for the most suitable housing based on predetermined criteria, increase user satisfaction and make a positive contribution to housing development in the Bogor area. As for the results of the research that has been carried out, we get bale asra housing with a value of 0.96, Budiman Asri Cimayang housing 0.7, Grand Vila Cahaya housing 0.72 and Mulia Land Bogor housing with a value of 1. So from these results it can be concluded that Mulia Land Bogor housing is the most suitable housing based on the criteria in the area. Bogor.